Operating Efficiency and A Test of Semi Strong Market Efficiency for Commercial Banks’ Stock Price in Nepal - Shrestha, Sabin; Bedari, Devi Prasad; Pant, Sabin (Janabhawana Research Journal, 2025)
Stock market efficiency needs to be gauged on a regular basis as the development of stock market affects the level of economic growth in the economy. The level of stock market efficiency determines the investment strategy of the investors as well. The purpose of this study is to test the commercial bank stock price semi strong form of efficiency. This study found that commercial banks’ stock prices are not semi form of market efficient. This study used the Data Envelopment Analysis (DEA) to examine the operational efficiency of the commercial bank. This study has used half yearly data of Nineteen periods to compute technical efficiency and its decomposition into pure and scale efficiency score of all Nepalese commercial banks and to test the semi form of market efficiency for commercial bank stock price. The operating efficiency score of the bank represents the public information for the current study. The current study used Arellano and Bover or Blundell and Bond model of dynamic panel regression to test the commercial stock price efficiency. This study found that change in log of lag one stock price and change in log of efficiency score can predict significantly the change in log of stock price. This implies that publicly available information has not been realized and adjusted in the current stock. This leads to the conclusion that Nepalese commercial bank stock price is not semi strong market efficient.